The Distribution of Meningioma in Dr. Hasan Sadikin General Hospital Bandung Period 2010–2013 - Stephanie Victoria Gunadi; Sri Suryanti; Raden Yohana (Faculty of Medicine Universitas Padjadjaran, 2018)
Background: In neurological diseases, brain tumor is the second leading cause of death after stroke, of which the most common types of brain tumor is meningioma. There are many factors affect the prognosis of meningioma patient, including age, gender, location, and histopathological type of tumor. This study aimed to explore the distribution of meningioma based on age, gender, location of the tumor, and its histopathological type during the period of 2010–2013 in Dr. Hasan Sadikin General Hospital Bandung.Methods: This study was a quantitative descriptive study and data were collected from medical records of Department of Pathology between January 2010-December 2013. Age, gender, location, and histopathological type of meningioma were acquired. Results: There were 277 eligible cases of meningioma with an average number of cases per year were 69 cases. The ratio of men to women was 1:6.4. Meningioma was most commonly found in the age group 4150 years (38.9%), and mostly located in convexity (55.96%). The most common histopathological type of meningioma was meningotheliomatous meningioma (70%).Conclusions: The frequency of meningioma is 6 times higher in women, predominantly around the age of 50 years old. Meningioma is most commonly found in convexity, and meningotheliomatous meningioma is the most common histopathological type.